Geostatistical seismic inversion and 3D modelling of metric flow units, porosity and permeability in Brazilian presalt reservoir - Penna, Rodrigo; Lupinacci, Wagner Moreira (Petroleum science, 2024)
Flow units (FU) rock typing is a common technique for characterizing reservoir flow behavior, producing reliable porosity and permeability estimation even in complex geological settings. However, the lateral extrapolation of FU away from the well into the whole reservoir grid is commonly a difficult task and using the seismic data as constraints is rarely a subject of study. This paper proposes a workflow to generate numerous possible 3D volumes of flow units, porosity and permeability below the seismic resolution limit, respecting the available seismic data at larger scales. The methodology is used in the Mero Field, a Brazilian presalt carbonate reservoir located in the Santos Basin, who presents a complex and heterogenic geological setting with different sedimentological processes and diagenetic history. We generated metric flow units using the conventional core analysis and transposed to the well log data. Then, given a Markov chain Monte Carlo algorithm, the seismic data and the well log statistics, we simulated acoustic impedance, decametric flow units (DFU), metric flow units (MFU), porosity and permeability volumes in the metric scale. The aim is to estimate a minimum amount of MFU able to calculate realistic scenarios porosity and permeability scenarios, without losing the seismic lateral control. In other words, every porosity and permeability volume simulated produces a synthetic seismic that match the real seismic of the area, even in the metric scale. The achieved 3D results represent a high-resolution fluid flow reservoir modelling considering the lateral control of the seismic during the process and can be directly incorporated in the dynamic characterization workflow.